Present and Future of Evolutionary Economics Japanese Perspectives - Yagi, Kiichiro; Shiozawa, Yoshinori; Aruka, Yuji; Nishibe, Makoto; Isogai, Akinori (Evolutionary Economics and Social Complexity Science, 2024)
VIII, 281 p. 36 illus., 25 illus. in color.